Project-Based Learning Model to Enhance Soft Skills of Vocational High School Students - Tejawiani, Ida; Lastriyani, Indri; Lidiawati, Lidiawati; Margono, Margono; Fitriyani, Ida Farida (Riviera Publishing, 2023)
This study aimed to analyze students' interpersonal and intrapersonal skills at Integrated Vocational High School 1 Yaspida, where all students are in boarding schools and SMK Yasti district. Sukabumi, only 15% are boarding houses. The method used is qualitative with case studies. The data analysis technique used is the Miles and Huberman technique (data reduction, data presentation, and conclusion). The results of this study indicate that the soft skills of students at SMK YASTI and SMK Terpadu 1 Yaspida have the same results; students' interpersonal and intrapersonal skills are not affected by the presence of students living, whether they are in boarding school or not. Yasti Vocational School has a very good program, which can shape student characteristics and develop student soft skills, just like students who are in Islamic boarding schools. The soft skills aspect with the highest rating is the Collaboration aspect, and the lowest rating is on the leadership aspect. This research implies that through the implementation of project-based learning models, vocational high schools (SMK) can create a more realistic learning environment that is outcome-oriented and focused on developing skills needed in the working world and daily life.